Transformasi Era Digitalisasi Dalam Membentuk Jiwa Leadership Pada Gen-Z Dan Millenial - Ari Prabowo; Yuli Arnida Pohan; Aisyah Azhar Adam; Nanda Fitria Aulanda; Shofyan Roni (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
The purpose of this activity is to provide insight into relevant leadership skills, increase adaptability, and empower students to lead effectively in a dynamic work environment. The important target of the seminar Transforming the Digitalization Era in Shaping the Spirit of Leadership in Gen-Z and Millennials is all students of the Potensi Utama University, study program in preparing the younger generation to become adaptive, innovative, inclusive, and ethical leaders in the digital era. Through increased understanding of technology, development of leadership skills, formation of a collaborative spirit, expansion of professional networks, and ethical awareness, this seminar is expected to produce future leaders who are ready to face the complexities and opportunities offered by the modern world of work. The method was conducted indoors using slides and presentations in front of the students. Several questions and answers about the material provided were held to facilitate all students in understanding and knowing more about the material that had been delivered previously. The implementation of community service activities took place in the Hall Building B, University of Main Potential Medan starting at 09.00 WIB until completion, attended by 400 student participants from all study programs at the University of Main Potential both offline and online (zoom). Activities in the form of direct delivery of material. The results of the seminar activities are that students are expected to develop adaptive and innovative skills in accordance with the demands of the times, students will also be able to recognize and overcome the challenges of digitalization, as well as implement effective leadership strategies, In addition, this seminar aims to expand the professional network of participants, so that they can collaborate and share experiences with peers. Overall, the seminar is expected to produce young leaders who are ready to face the dynamics and complexities of the modern working world.